2023
DOI: 10.3389/fpsyt.2023.1205119
|View full text |Cite
|
Sign up to set email alerts
|

Dense attention network identifies EEG abnormalities during working memory performance of patients with schizophrenia

Ruben Perellón-Alfonso,
Aleš Oblak,
Matija Kuclar
et al.

Abstract: IntroductionPatients with schizophrenia typically exhibit deficits in working memory (WM) associated with abnormalities in brain activity. Alterations in the encoding, maintenance and retrieval phases of sequential WM tasks are well established. However, due to the heterogeneity of symptoms and complexity of its neurophysiological underpinnings, differential diagnosis remains a challenge. We conducted an electroencephalographic (EEG) study during a visual WM task in fifteen schizophrenia patients and fifteen h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…Another study suggested that α wave as α lateralization plays a causal role in attention tasks [ 23 , 24 ]. Conversely, patients with schizophrenia, who typically exhibit deficits in working memory, showed significantly lower α suppression in the task preparation, memory encoding, maintenance, and retrieval phases, indicating strong α power [ 25 ], whereas stronger connections in δ, β, and γ bands were found in the depressive emotion group [ 10 ]. These results may imply that attentional network might be modulated due to mental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Another study suggested that α wave as α lateralization plays a causal role in attention tasks [ 23 , 24 ]. Conversely, patients with schizophrenia, who typically exhibit deficits in working memory, showed significantly lower α suppression in the task preparation, memory encoding, maintenance, and retrieval phases, indicating strong α power [ 25 ], whereas stronger connections in δ, β, and γ bands were found in the depressive emotion group [ 10 ]. These results may imply that attentional network might be modulated due to mental conditions.…”
Section: Discussionmentioning
confidence: 99%